2022
DOI: 10.1002/mde.3671
|View full text |Cite
|
Sign up to set email alerts
|

Imports, technology, and employment: Job creation or creative destruction

Abstract: This study examines the employment impact of technology by using firm‐level survey data for a large number of developing countries. We not only examine the impact of technology on overall employment but also investigate the effect on different types of employment, such as skilled, unskilled, temporary, and seasonal. Considering asymmetric distribution of employment, we utilize quantile regression for empirical analysis. Our findings unequivocally suggest that technology does not kill jobs. Further, we could no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 58 publications
(87 reference statements)
1
11
0
Order By: Relevance
“…Next, we compared our findings to those of previous studies and found that these are consistent with a few. Sharma and Mishra (2023) provide evidence, for instance, that in emerging nations, technological progress leads to increased employment opportunities. Our findings are consistent with theirs, showing that technology from several sources improves efficiency, increases learning, and boosts employment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, we compared our findings to those of previous studies and found that these are consistent with a few. Sharma and Mishra (2023) provide evidence, for instance, that in emerging nations, technological progress leads to increased employment opportunities. Our findings are consistent with theirs, showing that technology from several sources improves efficiency, increases learning, and boosts employment.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, firms can benefit from importing capital goods (a proxy for technical progress) and influence employment. Thus, trade openness can enhance the size of operations and technological innovation, further impacting employment (Sharma & Mishra, 2023). Furthermore, it is imperative to assess technological progress effects on employment level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, to depict the varied impact of international trade at different levels of employment and wages, we deploy quantile‐based regression. We follow an approach similar to Sharma and Mishra (2023) to depict the distribution of employment impact. The quantile technique helps gauge the impact of independent variables on the range of distribution of outcome variables (Powell & Wagner, 2014; Qin et al, 2023).…”
Section: Empirical Strategy: Model and Methodologymentioning
confidence: 99%
“…The survey provides a detailed analysis of the business environment of the firms that represent the private sector of the economies around the world regarding their infrastructure and services, competition existing in their respective industries, management practices, and obstacles faced by these firms in terms of financial access, corruption, political instability, crime and other external factors, capacity, labor performance, and so forth. The survey also provides information regarding firm‐level characteristics such as size, ownership concentration, demography, and organization structure (see Sharma & Mishra, 2022). The establishments are selected in such a manner that they represent the private sector of the economies.…”
Section: Data and Stylized Factsmentioning
confidence: 99%